Numerical Analysis of Openings in Stiffeners under Impact Loading: Investigating Structural Response and Failure Behavior - Ridwan Ridwan; Sudarno Sudarno; Haris Nubli; Achmad Chasan; Iwan Istanto; Pandu Sandi Pratama (Universitas Sebelas Maret, 2023)
As the demand for lightweight ships continues to rise, there is a growing necessity to explore innovative methods that can reduce the weight of ship structures without altering the materials used. This research addresses this challenge by investigating the effect of opening in stiffener under impact loading. The research aims to provide valuable insights into optimizing weight reduction strategies while ensuring the ship's overall strength and performance remain uncompromised. To achieve this goal, the study employed the finite element method as a solver. By simulating impact scenarios and analyzing stiffener responses, the numerical analysis quantified the structural behavior and failure modes. The focus was on understanding the impact of openings on the structural integrity and how it relates to their positioning relative to the impact point. The results of the study indicate that opening slightly distant from the impact point exhibit greater strength, showcasing a counterintuitive relationship between opening placement and structural response.